Replacing a part of wheat flour with starchy food containing high levels ofresistant starch in noodles processing - Kieu Minh Vuong; N.B. Tram; L.N. Tuyen; L.T.T. Vy; Ngô Văn Tài; Nguyễn Minh Thủy (Food Research, 2022)
Resistant starch has been shown to be associated with many health benefits. The study was conducted to analyze amylose and resistant starch content in selected starchy materials (black beans, red beans, green Xiem bananas, and potatoes) and investigate the influence of their flour/starch mixing ratio on the quality of noodles. The microstructure of noodles was analyzed by scanning electron microscopy. The results showed that potato starch had the highest resistant starch content (56.70%), followed by green Xiem banana flour (41.55%), black bean flour (16.51%), and red bean flour (15.55%). The raw materials with higher resistant starch also had higher amylose content. Amylose content, resistant starch content, and hardness of noodles increased when partly replacing wheat flour with the high level of RS flours/starches in the formulation. The data rank some tests revealed that formula A3 (replacing 50% of wheat flour with other starchy food containing high levels of resistant starch) was chosen due to the product containing relatively high RS content (14.78%), well structured and well accepted by panellists. The texture of the cooked noodles was assessed to be similar to that of the control sample (100% wheat flour). This study proved that it is possible to elaborate noodles to replace a part of wheat flour with starchy food containing high levels of the well-accepted formulation.
Keywords: Food composition and properties; Phytase and its Applications; Cassava research and cyanide